Performance analysis of antenna correlation on land mobile satellite based MIMO systems - Yuan LIN; Yuan-zhi HE; Jing-chao WANG; Han HAN (Tongxin xuebao)
The joint effect of spatial correlation and shadowing of channels on the performance of land mobile satellite MIMO system was analyzed.With the help of contour integral,residue theorem and integral of special functions,closed-form approximations of the outage probability (OP) and the average symbol error rate (SER)were derived.The Monte Carlo simulations results were illustrated through several examples in order to assess the impact of correlation coefficient,the number of antenna and different modulation mode on the performance.It shows that although channel correlation and shadowing degrade system gain,significant performance gains can be obtained by multi-satellite MIMO systems compared to relevant single-input single-output (SISO) ones.